2021
DOI: 10.3390/cells10061465
|View full text |Cite
|
Sign up to set email alerts
|

Cell–Cell Fusion and the Roads to Novel Properties of Tumor Hybrid Cells

Abstract: The phenomenon of cancer cell–cell fusion is commonly associated with the origin of more malignant tumor cells exhibiting novel properties, such as increased drug resistance or an enhanced metastatic capacity. However, the whole process of cell–cell fusion is still not well understood and seems to be rather inefficient since only a certain number of (cancer) cells are capable of fusing and only a rather small population of fused tumor hybrids will survive at all. The low survivability of tumor hybrids is attri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 127 publications
(287 reference statements)
2
18
0
Order By: Relevance
“…Albeit syncytin-1 was reported to improve the prognosis of breast cancer patients [65], most data from other carcinoma types rather indicated a relationship between syncyctin-1 and tumor progression [59,61,64,66]. These findings also suggested that fusion of cancer cells in general develops a more malignant phenotype with progression of metastatic lesions [16,20,22,99,167,169,170,172]. Further involvement of syncytin-1 in the fusion of two non-transformed cells undergoing a malignant conversion has not yet been reported and, hence, remains ambiguous.…”
Section: Syncytin-1mentioning
confidence: 99%
See 3 more Smart Citations
“…Albeit syncytin-1 was reported to improve the prognosis of breast cancer patients [65], most data from other carcinoma types rather indicated a relationship between syncyctin-1 and tumor progression [59,61,64,66]. These findings also suggested that fusion of cancer cells in general develops a more malignant phenotype with progression of metastatic lesions [16,20,22,99,167,169,170,172]. Further involvement of syncytin-1 in the fusion of two non-transformed cells undergoing a malignant conversion has not yet been reported and, hence, remains ambiguous.…”
Section: Syncytin-1mentioning
confidence: 99%
“…Fusion also includes infection of host cells with enveloped viruses [19] and tumor development [20,21]. Even though the process of cell fusion appears phenomenologically simple, like two merging soap bubbles, it is tightly regulated whereby various molecular processes remain to be elucidated [22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another potential concern comes from a longstanding model that cell fusion, particularly fusion induced by viruses, contributes to cancer development, progression, metastasis, recurrence, dormancy, and acquired drug resistance (reviewed in: [39,[63][64][65]). This model has been supported by recent reports of cell hybrids in human cancers, [58,66] by multiple observations in animal models (reviewed in: [39,65,67,68]), by findings that human cells can be made cancerous through cell fusion, [59,69,70] and by comparing the evolution of tumors and cell hybrids [71]. However, whether any neoplastic hybrids found in humans [58] are made by viral fusogens, as has been suggested [72][73][74], is yet to be determined.…”
Section: Cell Fusion and Neoplasiamentioning
confidence: 99%